Effectiveness of short video education on primigravida's knowledge of colostrum benefits at Puskesmas Kelayan Timur, Banjarmasin - Istiqamah; Zulliati; Meldawati; Sari, Anita (Ananda - Health & Education Foundation, 2026)
Background: Suboptimal breastfeeding practices, often stemming from inadequate maternal knowledge and cultural misconceptions, contribute significantly to neonatal morbidity and mortality. This is particularly prevalent among primigravida women, who lack prior experience. In areas like Kelayan Timur, Banjarmasin, where early initiation of breastfeeding coverage is critically low (36.4%), innovative educational interventions are urgently needed. Objective: This study aimed to evaluate the effectiveness of a short video education intervention in improving knowledge about the benefits of colostrum among primigravida women. Method: A pre-experimental one-group pretest-posttest design was employed. A total of 15 primigravida women from Puskesmas Kelayan Timur were recruited via accidental sampling. Participants completed a validated 6-item knowledge questionnaire (Cronbach's alpha = 0.753), watched a 60-second educational video about colostrum benefits, and immediately retook the questionnaire. Knowledge was categorized as poor (<56%), sufficient (56-75%), or good (76-100%). Data were analyzed using descriptive statistics and the Wilcoxon Signed-Rank Test due to non-normal data distribution. Results: The majority of participants were at low-risk age (20-35 years; 80.0%), had mid-low education (86.7%), and were unemployed (80.0%). Pretest results showed most respondents had insufficient knowledge (poor: 46.7%; sufficient: 33.3%; good: 20.0%). Post-test results revealed a significant improvement, with the majority achieving good knowledge (80.0%). The Wilcoxon test confirmed a statistically significant increase in knowledge scores (p-value = 0.004). Conclusion: A short video education intervention significantly improved knowledge about colostrum benefits among primigravida women. This accessible and standardized tool shows great potential for integration into routine antenatal care to bridge knowledge gaps, thereby supporting better breastfeeding practices and improved neonatal health outcomes.